Handbook of multiple comparisons - Cui, Xinping; Dickhaus, Thorsten-Ingo; Ding, Ying; Hsu, Jason C. (Chapman & Hall/CRC handbooks of modern statistical methods, 2022)
Written by experts that include originators of some key ideas, chapters in the Handbook of Multiple Testing cover multiple comparison problems big and small, with guidance toward error rate control and insights on how principles developed earlier can be applied to current and emerging problems. Some highlights of the coverages are as follows.Error rate control is useful for controlling the incorrect decision rate. Chapter 1 introduces Tukey's original multiple comparison error rates and point to how they have been applied and adapted to modern multiple comparison problems as discussed in the later chapters. Principles endure. While the closed testing principle is more familiar, Chapter 4 shows the partitioning principle can derive confidence sets for multiple tests, which may become important as the profession goes beyond making decisions based on p-values.Multiple comparisons of treatment efficacy often involve multiple doses and endpoints.